2020
DOI: 10.3390/app10176031
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Prediction of Roadway Broken Rock Zone Based on a Novel Hybrid Soft Computing Model Using Gaussian Process and Particle Swarm Optimization

Abstract: A simple and accurate evaluation method of broken rock zone thickness (BRZT), which is usually used to describe the broken rock zone (BRZ), is meaningful, due to its ability to provide a reference for the roadway stability evaluation and support design. To create a relationship between various geological variables and the broken rock zone thickness (BRZT), the multiple linear regression (MLR), artificial neural network (ANN), Gaussian process (GP) and particle swarm optimization algorithm (PSO)-GP method were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…In [24], GP was hybridized with particle swarm optimization (PSO) to do advanced prediction of roadway broken road zone based on data collected in China. The study inferred that the hybrid model showed the best performance with higher variance accounted for (VAF), higher coefficient of determination (R 2 ), and lower root mean squared error (RMSE) compared to the other methods such as multiple linear regression (MLR) and artificial neural network (ANN).…”
Section: Gaussian Processmentioning
confidence: 99%
“…In [24], GP was hybridized with particle swarm optimization (PSO) to do advanced prediction of roadway broken road zone based on data collected in China. The study inferred that the hybrid model showed the best performance with higher variance accounted for (VAF), higher coefficient of determination (R 2 ), and lower root mean squared error (RMSE) compared to the other methods such as multiple linear regression (MLR) and artificial neural network (ANN).…”
Section: Gaussian Processmentioning
confidence: 99%
“…e Gaussian process (GP) can find a relationship between the input variable value and the output variable value of the training datasets, and the predicted output variable value of the testing datasets can be calculated using the created relationship. According to the study of Yu et al [35], Arthur et al [79], and Fang et al [36], a GP model can be determined by the mean function m(x) and covariance function k(x, x′), and that model f(x) is defined as follows:…”
Section: Gaussian Process (Gp)mentioning
confidence: 99%
“…Meanwhile, the successful application in solving the classical engineering design problem [31], airfoil design for aero vehicles problem [31], the strength of fiber-reinforced cemented paste backfill [32], and the compressive strength of concretes [33] also proves the high capacity of SSA. Besides, the Gaussian process was found to be an effective prediction technique after be used in landslide cases [34], broken rock zone prediction [35], carbon dioxide emission prediction [36], etc. Meanwhile, the conclusion that the GP performance can be improved after using the metaheuristic algorithm has been proved after many combinations such as PSO-GP [35] and GA-PSO [34] were proposed and tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in Reference [27] mentioned that the GP is capable of decreasing the complexity of the computer vision with a finer performance of reconstructions. In addition, researchers in Reference [28] compared the performance of an improved GP model with other methods, such as multiple linear regression (MLR) and artificial neural network (ANN), in predicting roadway broken road zone. The results showed that the hybrid model gave the best performance in terms of coefficient of determination (R 2 ), root mean squared error (RMSE), and variance accounted for (VAF).…”
Section: Stochastic Process-gaussian Processmentioning
confidence: 99%